Optimization of Calculating Invariants in Petri Nets to Support the Creation of Integration Testing Scenarios - M. G. Dorrer (Modelirovanie i Analiz Informacionnyh Sistem, 2015)
The article describes a method of finding business process invariants basing on a given model in eEPC notation. The method uses an original translation process to build a Petri net corresponding to the source eEPC model, to find its invariants and to translate them back into the eEPC notation. An optimized method of finding Petri net invariants is also offered, based on estimating possible values for separate vector elements (and a group of elements) and combining these values with each other to receive a Petri net invariant. The resulting business process invariants may be used to create integration testing scenarios for an implemented automation system.